(untitled) (Res Medica, 2014)
“ Every Child a Wanted Child” — this was the stated ambition of a campaign launched by the Family Planning Association in June, 1969. Few enlightened people would disagree with this ideal, yet the majority give little thought as to how it can be achieved and most are quite unaware of how difficult it is for women, especially among the lower social groups, to obtain advice on contraception. Millions of pounds are spent each year in anattempt to stop the world population explosion, but in Great Britain, one of the most densely populated countries in the world and one which boasts of its Welfare Services, free Family Planning advice is available to only a small percentage of women. It is estimated that in Scotland as few as 25-35% of pregnancies are planned. One in three of babies born to mothers under the age of 20 are conceived before marriage. The illegitimacy rate is rising steadily. Add to these the number of abortions which are induced therapeutically or illegally each year and a dismal picture of unplanned pregnancy emerges.